Estimasi Sumberdaya Batubara berdasarkan Data Ekplorasi Pengeboran dan Geophysical Logging pada Pt.Ansaf Job Site Pt.X Kalimantan Timur - A. Agus Mantri; Windhu Nugroho; Albertus Juvensius Pontus; Shalaho Dina Devy; Koeshadi Sasmito (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2026)
At the research location at PT. Ansaf Inti Resource, there are several mining stages such as exploration. In the exploration itself, drilling and logging activities are carried out. However, if not careful in calculating coal resource estimates, there can be potential discrepancies between the estimated coal resources based on the results of drilling data identification and well logging data with the actual results. Exploration activities are activities that are often carried out by companies to determine reserves in an area. Without carrying out these activities, companies will have difficulty estimating the profits to be obtained. To obtain the data needed to carry out exploration activities such as calculating the quality and quantity of coal, it is necessary to carry out drilling such as the full coring method and also carry out logging activities to complete the data and also as comparative data from core drilling. Coal Resources are part of a coal deposit in the form of a certain quantity and have reasonable prospects that allow for economic consideration. Coal resources are divided according to the level of geological confidence into inferred, indicated, and measured categories. Therefore, in this study, the author will calculate coal resources from exploration data collection such as coring data, cutting data, and well logging data as well as coal quality data and process it in Minescape 5.7 software so that it can obtain an estimate of coal resources for each seam at the research location.